2021
DOI: 10.1139/cjpp-2020-0522
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of pulmonary CT lesions and associated bronchiectasis in 115 convalescent patients with novel coronavirus pneumonia (COVID-19) in China

Abstract: A total of 115 convalescent inpatients with COVID-19 were enrolled. According to the results of scans of lung lesions via computed tomography (CT), the patients were divided into mild, moderate, and severe groups. The clinical data of the patients were collected, including age, gender, finger pulse oxygen pressure, ventricular rate, body temperature, etc. The correlation between the clinical indicators and the lesions of high-resolution CT (HRCT) and bronchiectasis was analyzed. Among the 115 patients, 82 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Radiological detection of bronchiectasis is frequent in the acute phase of COVID-19, and may even represent a factor of its severity. 87 , 88 , 89 In addition, there are frequent sequelae in patients who have overcome the infection, 90 , 91 although their long-term clinical repercussion is unknown. 92 The literature on the incidence or severity of COVID-19 in patients with pre-existing bronchiectasis is scarce, probably due to the low proportion of these patients in the published series on COVID-19 patients.…”
Section: Bronchiectasismentioning
confidence: 99%
“…Radiological detection of bronchiectasis is frequent in the acute phase of COVID-19, and may even represent a factor of its severity. 87 , 88 , 89 In addition, there are frequent sequelae in patients who have overcome the infection, 90 , 91 although their long-term clinical repercussion is unknown. 92 The literature on the incidence or severity of COVID-19 in patients with pre-existing bronchiectasis is scarce, probably due to the low proportion of these patients in the published series on COVID-19 patients.…”
Section: Bronchiectasismentioning
confidence: 99%
“…The role of severe acute respiratory syndrome coronarvirus-2 (SARS-CoV-2) as the aetiology of bronchiectasis has been suggested by an observational study (78). Nearly 30% of in-patients with COVID-19 developed radiologic evidence of bronchiectasis at convalescence, and the area of severely infected regions correlated with a greater probability of developing bronchiectasis (78). What were the key events driving the bronchial dilation remained unclear.…”
Section: Impact Of Covid-19 On the Clinical Outcomes And Management O...mentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) has resulted in a global pandemic related to the transmission of various variants, causing substantial morbidity and mortality. The role of severe acute respiratory syndrome coronarvirus-2 (SARS-CoV-2) as the aetiology of bronchiectasis has been suggested by an observational study [ 78 ]. Nearly 30% of inpatients with COVID-19 developed radiological evidence of bronchiectasis at convalescence, and the area of severely infected regions correlated with a greater probability of developing bronchiectasis [ 78 ].…”
Section: Impact Of Covid-19 On the Clinical Outcomes And Management O...mentioning
confidence: 99%
“…The percentage of patients with BE observed in the early phase of pneumonia is highly variable, according to the studies undertaken (6.3-52.0%). [35][36][37][38][39][40][41][42] Bao et al [20] performed a systematic review with meta-analysis to provide a more accurate estimate of the detection of COVID-19 by chest computed tomography (CT) and reported the most common findings in imaged chest CT. The results showed that although ground-glass opacity was, as expected, the most common CT feature to be detected, in 83.3% of 2738 cases, BE was observed in only 5.4% of cases.…”
Section: Be and The Acute Phase Of Covid-19 Pneumoniamentioning
confidence: 99%